2019
DOI: 10.1002/jsfa.9917
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory potential of prickly pears and their isolated bioactives against digestive enzymes linked to type 2 diabetes and inflammatory response

Abstract: BACKGROUND Prickly pears are potential candidates for the development of low‐cost functional foods because they grow with low water requirements in arid regions of the world. They are sources of betalains and phenolic compounds, which have been reported to contribute to human health. The study of the biological activity of different varieties and of their isolated bioactive constitutes is fundamental in the design of functional foods. In this context, our objective is the assessment of the ability of Spanish a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 40 publications
3
17
0
1
Order By: Relevance
“…Dillenii samples have different amounts of flavonoids, IG1 and IG2, together with QG1. Additionally, the in vitro antioxidant, anti-inflammatory, and anti-hyperglycemic activities of isolated, purified, and semi-synthesized betalains and phenolic compounds from Opuntia ficus-indica prickly pear fruits have been recently reported by Gómez-Maqueo et al [ 32 ]. Additionally, some authors reported that Opuntia extracts are hepatoprotective and can be used as a nutraceutical to prevent Acetaminophen (APAP)-induced acute liver failure (ALF), which is a serious health problem in developed countries [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dillenii samples have different amounts of flavonoids, IG1 and IG2, together with QG1. Additionally, the in vitro antioxidant, anti-inflammatory, and anti-hyperglycemic activities of isolated, purified, and semi-synthesized betalains and phenolic compounds from Opuntia ficus-indica prickly pear fruits have been recently reported by Gómez-Maqueo et al [ 32 ]. Additionally, some authors reported that Opuntia extracts are hepatoprotective and can be used as a nutraceutical to prevent Acetaminophen (APAP)-induced acute liver failure (ALF), which is a serious health problem in developed countries [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 1d, it is characterized by a high IG1 and IG5 content, but additionally contains peak 26 (Rt = 42.5; λ max at 255 and 355 nm), which we identified as isorhamnetin hexosyl-rhamnoside for the first time in prickly pear fruits. Following the abbreviation of isorhamnetin glycosides purified from cacti [18,19], we abbreviated this compound as IG7. This last isorhamnetin glycoside could be an isomer of IG5, however more information is needed to elucidate its structure.…”
Section: Identification Of Betalains and Phenolic Compoundsmentioning
confidence: 99%
“…* Indicates statistically significant differences (p ≤ 0.05) in bioaccessibility between Pelota and Sanguinos varieties. 1 Data previously reported [11], 2 isorhamnetin glucosyl-rhamnosyl-rhamnoside (IG1), 3 isorhamnetin glucosyl-rhamnosyl-pentoside (IG2), 4 isorhamnetin hexosyl-hexosyl-pentoside (IG3), 5 isorhamnetin glucosyl-pentoside (IG4), 6 isorhamnetin glucosyl-rhamnoside (IG5).…”
Section: Bioaccessibility Of Betalains and Phenolic Compounds In Hhp-treated Peelsmentioning
confidence: 99%
“…mg/100 g fresh weight, 2 isorhamnetin glucosyl-rhamnosyl-rhamnoside (IG1), 3 isorhamnetin glucosyl-rhamnosyl-pentoside (IG2), 4 isorhamnetin hexosyl-hexosyl-pentoside (IG3), 5 isorhamnetin glucosyl-pentoside (IG4), and 6 isorhamnetin glucosyl-rhamnoside (IG5).…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation